Smart ungual biopenetrant from the roots of Beta vulgaris - Madhav, Satheesh; Singh, Kirti (Journal of Applied Pharmaceutical Research, 2017)
The main objective of the current research was to isolate biopenetrant from Beta vulgaris and formulate bioadhesive layers loaded with terbinafine using this biopenetrant for delivery through nail. Form the preparation of films, Rosa centifolia and Vitis vinifera were used as a biopolymer. Beta vulgaris was used as biopenetrant. The formulations prepared using Beta vulgaris biopenetrant were compared with formulations containing papain as standard penetrant. Four bio-adhesive films of different ratios were prepared by film casting method using each penetrant. The formulated films were evaluated for various parameters like weight, thickness, nail adhesivity, content uniformity, surface pH, folding endurance, and in-vitro drug permeation. The formulation LB4 (containing 1:4 Beta vulgaris biopenetrant) was found to be the best formulation having R2 value 0.990 with zero order as best fit model. The results obtained conclude that biopenetrants can be used as natural penetration enhancers.